Nuclear responses to astrophysical neutrinos through the neutral Gamow-Teller strength - Tsakstara, V.; Kosmas, T. S. (HNPS Advances in Nuclear Physics, 2012)
We study nuclear responses to low-energy neutrinos through the neutral Gamow- Teller strength B(GT0). As a concrete example we adopt the 56Fe isotope which plays important role in core collapse supernova. By using the quasi-particle RPA method we found that this strength is mainly concentrated on the resonance at around 10 MeV. Within the QRPA, we may also examine the changes in B(GT0) induced by non-zero values of the momentum transfer in astrophysical neutrino scattering on nuclei.